Digital vs. Film Fundus Photography for Research Grading of Diabetic Retinopathy Severity (2010)
ABSTRACT: Purpose.: To assess agreement between digital and film photography for research classification of diabetic retinopathy severity. Methods.: Digital and film photographs from a 152-eye cohort with a full spectrum of Early Treatment Diabetic Retinopathy Study (ETDRS) severity levels were assessed for repeatability of grading within each image medium and for agreement on ETDRS discrete severity levels, ascending severity thresholds, and presence or absence of diabetic retinopathy index lesions, between digital and 35-mm slides (film). Digital photographs were color balanced to match film. Results.: There was substantial agreement (κ = 0.61, κw [linear weighted] = 0.87) in classification of ETDRS diabetic retinopathy severity levels between digital images and film. Marginal homogeneity analyses found no significant difference in frequency distributions on the severity scale (P = 0.21, Bhapkar test). The κ results ranged from 0.72 to 0.95 for presence or absence of eight ascending diabetic retinopathy severity thresholds. Repeatability of grading between readers viewing digital images was equal to or better than that obtained with film (pair-wise interreader κ for digital images ranged from 0.47 to 0.57 and for film from 0.43 to 0.57. The κ results for identifying diabetic retinopathy lesions ranged from moderate to almost perfect. Moderate agreement of intraretinal microvascular abnormalities and venous beading between digital images and film accounted for slightly lower concordance for severity thresholds ≥47 and for slightly lower interreader agreement within digital and film images at severity thresholds ≥43 and ≥47. Conclusions.: Under controlled circumstances, digital photography can equal the reliability of 35-mm slides for research classification of ETDRS severity level.